Measuring the Resilience of Indonesian Communities to Disaster - Yulinda Erma Suryani; Dwi Wahyuni Uningowati (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
In psychology, there are several concepts regarding toughness, namely: resilience, hardiness and grit. The concept of resilience and its measuring instruments are the result of adaptation of theories from abroad that cannot be directly applied in Indonesia, because there are fundamental differences in the life order of Indonesian society, so it is necessary to develop tools or instruments to measure the resilience of Indonesian society. This research was conducted using a qualitative approach. The data collection method used was literature study, in the form of primary literature and secondary literature. The data analysis method used is content analysis. The concepts of resilience, hardiness, and grit cannot be applied directly in Indonesia, because there are fundamental differences in the life order of Indonesian society. There are two things that must be considered in drafting the resilience concept of Indonesian society, namely the issue of specific long-term goals and the issue of focus.